A manganese-containing organic-inorganic hybrid material and its preparation method and application

By using (C6H15ClNO)2MnBr4 organic-inorganic hybrid material, and using solvent solutions of (3-chloro-2-hydroxypropyl)trimethylammonium chloride, manganese bromide and hydrobromic acid, the problem that existing materials are difficult to have high luminescence quantum yield and long luminescence lifetime at the same time, and excellent photoluminescence performance is achieved, which is suitable for the production of photoluminescence devices.

CN115521775BActive Publication Date: 2025-03-21FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110706234.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-24
Publication Date
2025-03-21
Estimated Expiration
2041-06-24

AI Technical Summary

Technical Problem

The existing organic-inorganic hybrid materials are difficult to have high luminescence quantum yield and long luminescence lifetime in terms of photoluminescence properties, which limits their development in practical applications.

Method used

(C6H15ClNO)2MnBr4 is used as a manganese-containing organic-inorganic hybrid material, and is prepared by spontaneous crystallization in the evaporation reaction of (3-chloro-2-hydroxypropyl)trimethylammonium chloride, manganese bromide and hydrobromic acid in solvent solution to obtain a crystal material with excellent photoluminescence properties.

Benefits of technology

This material can emit 516nm of strong green light under 375nm ultraviolet light excitation, with a fluorescence life of 363μs and a quantum yield of 65-70%. It is suitable for the production of photoluminescent devices and has high practicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115521775B_ABST
    Figure CN115521775B_ABST
Patent Text Reader

Abstract

This invention discloses a manganese-containing organic-inorganic hybrid material, its preparation method, and its application. The manganese-containing organic-inorganic hybrid material is based on (C6H...) 15 ClNO)2MnBr4 indicates that the manganese-containing organic-inorganic hybrid material is a crystalline material belonging to the monoclinic crystal system with space group C2 / c and cell parameters β = 129.634(6)° and γ = 90°. The preparation method of the crystalline material of this invention is simple and convenient. The crystalline material provided by this invention can emit strong green light under ultraviolet light excitation, with a fluorescence lifetime of up to 363 μs and a quantum yield as high as 68.47%. Therefore, it can be used to fabricate photoluminescent devices and has high practicality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and specifically relates to an organic-inorganic hybrid material containing manganese, a preparation method and an application thereof. Background Art

[0002] Organic-inorganic hybrid materials are widely used in many fields such as optics, microelectronics, environment, and energy storage due to their diverse structures, interesting optical, electrical, and magnetic properties. The organic and inorganic components in organic-inorganic hybrid materials are self-assembled by bonds or interpenetrating network structures at the molecular scale, making them a multifunctional composite material. In order to obtain organic-inorganic hybrid multifunctional materials and explore the relationship between their intrinsic structure and various properties, researchers have conducted a large number of exploratory experiments.

[0003] In recent years, organic-inorganic hybrid materials have attracted extensive attention from researchers due to their excellent photoluminescent properties, which have potential application value in the fields of information storage, decoration, switching, and national defense. At present, researchers are mainly focusing on the synthesis of new photoluminescent organic-inorganic hybrid materials, which have high quantum yields and long luminescence lifetimes.

[0004] Among them, the excellent luminescence properties of lead-based hybrid materials and copper (I)-based hybrid materials were first discovered. Their high-energy emission in the visible light region and adjustable color range have attracted much attention. However, the biological toxicity of lead and the instability of monovalent copper ions limit their application and development in practice. Therefore, researchers have tried to replace toxic Pb with other metal ions. 2+ and unstable Cu + , thereby improving the application value of the material. However, few of these new hybrid materials have both high luminescence quantum yield and long luminescence lifetime. Therefore, how to prepare organic-inorganic hybrid materials with both high luminescence quantum yield and long luminescence lifetime has become a technical problem to be solved in this field. Summary of the invention

[0005] In order to improve the above technical problems, the present invention provides a manganese-containing organic-inorganic hybrid material, which is (C6H 15 ClNO)2MnBr4.

[0006] According to an embodiment of the present invention, the molecular weight of the manganese-containing organic-inorganic hybrid material is 679.86 and the density is 1.82 g / cm 3 .

[0007] According to an embodiment of the present invention, the manganese-containing organic-inorganic hybrid material is a crystalline material, the crystalline material belongs to the monoclinic system, the space group is C2 / c, and its unit cell parameters are α=90°, β=129.634(6)°, γ=90°.

[0008] According to an embodiment of the present invention, the unit cell volume of the crystalline material is

[0009] According to an embodiment of the present invention, the number of molecules in a unit cell of the crystalline material is Z=4.

[0010] According to an embodiment of the present invention, the F(000) of the crystalline material is 1324.

[0011] According to an embodiment of the present invention, the crystalline material has substantially Figure 1 The molecular structure is shown.

[0012] According to an embodiment of the present invention, the crystalline material is a green transparent bulk material, preferably a millimeter-scale transparent bulk material, wherein the millimeter-scale means that the size in at least two dimensions is at least 1 mm.

[0013] According to an embodiment of the present invention, the crystalline material has substantially Figure 5 X-ray crystal diffraction pattern shown.

[0014] According to an embodiment of the present invention, the crystalline material has substantially Figure 6 Fluorescence excitation and emission spectra are shown.

[0015] According to an embodiment of the present invention, the crystalline material has substantially Figure 7 Fluorescence lifetime spectrum is shown.

[0016] According to an embodiment of the present invention, the excitation spectrum of the crystalline material has a maximum excitation characteristic peak in the wavelength range of 355-395 nm, preferably has a maximum excitation characteristic peak at 375 nm.

[0017] According to an embodiment of the present invention, the emission spectrum of the crystalline material has a maximum emission characteristic peak in the wavelength range of 500-550 nm, preferably has a maximum emission characteristic peak at 516 nm.

[0018] According to an embodiment of the present invention, the fluorescence lifetime spectrum of the crystal material shows that the fluorescence lifetime at 516 nm is 363 μs, that is, the crystal material emits green fluorescence at 516 nm under the excitation of 375 nm ultraviolet light, and the fluorescence lifetime is 363 μs.

[0019] According to an embodiment of the present invention, the quantum yield of green fluorescence of the crystalline material is 65-70%, exemplified by 65%, 68.47%, and 70%.

[0020] According to an embodiment of the present invention, the crystalline material begins to decompose at 240-250° C., exemplarily at 245° C. Preferably, the crystalline material has a substantially Figure 8 Thermogravimetric curve shown.

[0021] The present invention also provides a method for preparing the above-mentioned manganese-containing organic-inorganic hybrid material and / or crystalline material, which comprises reacting (3-chloro-2-hydroxypropyl)trimethylammonium chloride, manganese bromide and hydrobromic acid through a solvent solution evaporation reaction and crystallization to obtain the manganese-containing organic-inorganic hybrid material and / or crystalline material.

[0022] According to an embodiment of the present invention, the molar ratio of (3-chloro-2-hydroxypropyl)trimethylammonium chloride, manganese bromide and hydrobromic acid is (1.5-2.5):1:(2-3), for example, 1.5:1:2, 2:1:2.5, 2.5:1:3; preferably 2:1:2.5.

[0023] According to an embodiment of the present invention, the manganese bromide may be selected from anhydrous manganese bromide and / or manganese bromide tetrahydrate, preferably manganese bromide tetrahydrate.

[0024] According to an embodiment of the present invention, the solvent may be at least one of methanol, ethanol and water, preferably methanol.

[0025] According to an embodiment of the present invention, the (3-chloro-2-hydroxypropyl) trimethylammonium chloride, manganese bromide and hydrobromic acid can be mixed in the form of their solutions before the solvent evaporation reaction, or (3-chloro-2-hydroxypropyl) trimethylammonium chloride solution, manganese bromide and hydrobromic acid can be added to methanol for mixing. For example, a methanol solution of manganese bromide and an aqueous solution of (3-chloro-2-hydroxypropyl) trimethylammonium chloride are first configured, and then the aqueous solution of (3-chloro-2-hydroxypropyl) trimethylammonium chloride and hydrobromic acid are sequentially added to the methanol solution of manganese bromide to obtain a mixed solution.

[0026] Preferably, the mixed solution of (3-chloro-2-hydroxypropyl)trimethylammonium chloride, manganese bromide and hydrobromic acid is stirred during preparation to completely dissolve the raw materials. For example, before the three solutions are mixed, the three solutions can be filtered separately. For another example, the three substances can be mixed first and then the mixed solution can be filtered.

[0027] For example, the filtration may be performed using a microporous membrane, preferably a membrane with a pore size of 0.05 to 1 μm.

[0028] According to an embodiment of the present invention, the concentration of the aqueous solution of (3-chloro-2-hydroxypropyl)trimethylammonium chloride may be 60-65%, exemplified by 60%, 62%, and 65%.

[0029] According to an embodiment of the present invention, the temperature of the solvent evaporation reaction is 25-40°C, preferably 30-40°C, exemplified by 30°C, 35°C, 40°C; more preferably 40°C.

[0030] According to an embodiment of the present invention, the solvent evaporation reaction is stopped until crystals are obtained. For example, the solvent evaporation reaction time is 24-60h, preferably 36-56h, and exemplarily 48h.

[0031] The present invention has no particular limitation on the total volume of the mixed solution. For example, the total volume of the mixed solution can be 15 to 30 mL according to the growth law of the crystal, and examples include 15 mL, 20 mL, 25 mL, and 30 mL.

[0032] According to an embodiment of the present invention, the manganese-containing organic-inorganic hybrid material (C6H 15 The preparation method of ClNO)2MnBr4 comprises the following steps:

[0033] Mix an aqueous solution of (3-chloro-2-hydroxypropyl)trimethylammonium chloride, a methanol solution of manganese bromide tetrahydrate and hydrobromic acid, and then evaporate and react to crystallize at 25-40°C for 24-60h to obtain (C6H 15 ClNO)2MnBr4 crystal material.

[0034] Specifically, the (C6H 15 The synthesis process of ClNO)2MnBr4 crystal material is as follows: 2(C6H 15 ClNO)Cl+2HBr+MnBr2·4H2O→(C6H 15 ClNO)2MnBr4+2HCl+4H2O.

[0035] The present invention also provides a manganese-containing organic-inorganic hybrid material or a crystal material thereof prepared by the above method.

[0036] The present invention also provides the use of the above-mentioned crystal material as a fluorescent material. For example, the fluorescent material is used in a photoluminescent device. For example, the photoluminescent device is used in an optical device.

[0037] The present invention also provides a fluorescent material, which contains the manganese-containing organic-inorganic hybrid crystal material.

[0038] The present invention also provides a photoluminescent device, which contains the manganese-containing organic-inorganic hybrid crystal material and / or fluorescent material.

[0039] The present invention also provides an optical device, which contains the manganese-containing organic-inorganic hybrid crystal material and / or the fluorescent material and / or the photoluminescent device.

[0040] Beneficial effects of the present invention:

[0041] (1) The present invention provides a (C6H 15 ClNO)2MnBr4 organic-inorganic hybrid material and crystal material thereof, wherein the crystal material is prepared by spontaneous crystallization after reaction of (3-chloro-2-hydroxypropyl)trimethylammonium chloride solution, manganese bromide and hydrobromic acid as raw materials. The preparation method of the invention is simple and easy to operate. The crystal material provided by the invention can emit strong green light under ultraviolet light excitation, has a long fluorescence lifetime, and can therefore be used to make photoluminescent devices.

[0042] (2) (C6H 15 ClNO)2MnBr4 crystal material can emit strong green light of 516nm under the excitation of 375nm ultraviolet light. The lifetime is as long as 363μs and the quantum yield is 68.47%. Therefore, it can be used to make photoluminescent devices and applied in optical devices, which has high practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The crystalline material (C6H 15 Structure and atomic numbering diagram of ClNO)2MnBr4.

[0044] Figures 2 to 4 The crystalline material (C6H 15 Unit cell stacking diagram of ClNO)2MnBr4 observed along different directions; among them, Figure 2 is the unit cell stacking diagram observed along the a-axis; Figure 3 is the unit cell stacking diagram observed along the b-axis; Figure 4 This is the unit cell stacking diagram observed along the c-axis.

[0045] Figure 5 The crystalline material (C6H 15 Measured (top) and simulated powder diffraction patterns (bottom) of ClNO)2MnBr4.

[0046] Figure 6 The crystalline material (C6H 15 Excitation and emission spectra of ClNO)2MnBr4 (the dotted line is the excitation spectrum; the actual line is the emission spectrum).

[0047] Figure 7 The crystalline material (C6H 15 Fluorescence lifetime spectrum of ClNO)2MnBr4.

[0048] Figure 8 The crystalline material (C6H15 Thermogravimetric curve of ClNO)2MnBr4.

[0049] Fig. 9 The crystalline material (C6H 15 Physical picture of ClNO)2MnBr4. DETAILED DESCRIPTION

[0050] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0051] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0052] Example 1

[0053] The aqueous solution evaporation method was used to grow (C6H 15 ClNO)2MnBr4 crystal material, the specific steps are as follows:

[0054] ① Dissolve 0.01 mol of manganese bromide tetrahydrate in 20 mL of methanol;

[0055] ② Add 5.0 mL of an aqueous solution containing 0.02 mol of (3-chloro-2-hydroxypropyl)trimethylammonium chloride (a 65% aqueous solution of (3-chloro-2-hydroxypropyl)trimethylammonium chloride) to the above methanol solution;

[0056] ③ Add 0.025 mol of hydrobromic acid to the above mixed methanol solution;

[0057] ④ filtering the mixed methanol solution obtained in step ③ through a filter membrane with a pore size of 1 μm;

[0058] ⑤ Place the above mixed solution in a petri dish and evaporate at 40℃ for 48h to obtain (C6H 15 ClNO)2MnBr4 crystal material.

[0059] The reaction equation is: 2(C6H 15 ClNO)Cl+2HBr+MnBr2·4H2O→(C6H 15 ClNO)2MnBr4+2HCl+4H2O.

[0060] Select the green transparent block crystals (such as Fig. 9The diffraction experiment was carried out on a MM007 small molecule single crystal diffractometer. Mo-Kα radiation was used at 293K. Data were collected in ω scanning mode. The results showed that the molecular weight of the crystals was 679.86 and the density was 1.82 g / cm 3 , F(000)=1324, belongs to the monoclinic system, the space group is C2 / c, and the unit cell parameters are α=90°,β=129.634(6)°,γ=90°,the unit cell volume is The number of molecules in the unit cell is Z = 4. Its crystal structure is as follows Figure 1 As shown, the unit cell stacking diagrams observed along different directions are as follows Figures 2 to 4 shown.

[0061] The obtained (C6H 15 ClNO)2MnBr4 crystals were ground into fine powder using an agate mortar and pressed into tablets. Powder X-ray diffraction data were collected on a Miniflex 600 diffractometer using Cu-Kα radiation with a scanning range of 5-50°. The powder diffraction pattern simulated by the data collected from the single crystal diffraction (below) was compared with the diffraction pattern obtained from the actual test (above). The results are shown in Figure 5 As shown in the figure, it can be seen from the results that the two are consistent in peak position, thus showing that the (C6H 15 ClNO)2MnBr4 crystalline material was successfully prepared with high purity.

[0062] The (C6H 15 The fluorescence excitation, emission and lifetime spectra of ClNO)2MnBr4 crystal samples were measured by FLS1000 steady-state / transient fluorescence spectrometer. The test results are shown in Figure 6 , Figure 7 shown. Figure 6 The results show that: (C6H 15 The ClNO)2MnBr4 crystal material can emit strong green light of 516nm under the excitation of 375nm ultraviolet light, which shows that the crystal material has good photoluminescence performance. Figure 7 The results show that: (C6H 15 The fluorescence lifetime of the ClNO)2MnBr4 crystal material at 516nm is 363μs, which indicates that the crystal material has a long fluorescence lifetime. The above spectral characteristics show that the (C6H 15 ClNO)2MnBr4 crystal material can be used to make photoluminescent devices for application in optical devices.

[0063] Example 2

[0064] The aqueous solution evaporation method was used to grow (C6H 15 The method of preparing the ClNO)2MnBr4 crystal material is basically the same as that of Example 1, except that the selected solvent is ethanol.

[0065] Example 3

[0066] The aqueous solution evaporation method was used to grow (C6H 15 The method of preparing the ClNO)2MnBr4 crystal material is basically the same as that of Example 1, except that the selected solvent is deionized water.

[0067] The crystalline materials obtained in Example 2-3 have substantially the same size, purity and properties as those in Example 1.

[0068] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a manganese-containing organic-inorganic hybrid material, characterized in that: Its (C6H 15 ClNO)2MnBr4; The method for preparing the manganese-containing organic-inorganic hybrid material comprises the following steps: The aqueous solution of (3-chloro-2-hydroxypropyl)trimethylammonium chloride solution, the methanol solution of manganese bromide tetrahydrate and hydrobromic acid are mixed, and then evaporated at 25-40°C for 24-60 hours to obtain (C6H 15 ClNO)2MnBr4 crystal material; The molar ratio of the (3-chloro-2-hydroxypropyl)trimethylammonium chloride, manganese bromide and hydrobromic acid is (1.5-2.5):1:(2-3).

2. The method for preparing the manganese-containing organic-inorganic hybrid material according to claim 1, characterized in that: The manganese-containing organic-inorganic hybrid material has a molecular weight of 679.86 and a density of 1.82 g / cm 3 .

3. The preparation method according to claim 1, characterized in that: The manganese-containing organic-inorganic hybrid material is a crystalline material, which belongs to the monoclinic system, has a space group of C2 / c, and has unit cell parameters of a=21.460(15)Å, b=9.670(5)Å, c=15.521(11)Å, α=90°, β=129.634(6)°, and γ=90°; The unit cell volume of the crystalline material is 2481(3)Å 3 ; The number of molecules in the unit cell of the crystal material is Z=4; The crystalline material has F(000)=1324.

4. The preparation method according to claim 3, characterized in that: The crystal material is a green transparent block material.

5. The method for preparing the manganese-containing organic-inorganic hybrid material according to claim 4, characterized in that: The crystal material is a millimeter-level transparent block material.

6. The preparation method according to any one of claims 1 to 3, characterized in that: The excitation spectrum of the crystal material has a maximum excitation characteristic peak within the wavelength range of 355-395nm; The emission spectrum of the crystalline material has a maximum emission characteristic peak within the wavelength range of 500-550nm; The fluorescence lifetime spectrum of the crystalline material shows that the fluorescence lifetime at 516 nm is 363 μs; The quantum yield of the crystalline material is 65-70%; The crystalline material starts to decompose at 240-250°C.

7. A fluorescent material, characterized in that: The fluorescent material comprises a manganese-containing organic-inorganic hybrid material prepared by the method according to any one of claims 1 to 6.

8. Use of the fluorescent material according to claim 7 in optical devices.

9. The use according to claim 8, characterized in that The fluorescent material is used in a photoluminescent device.

10. A photoluminescent device, characterized in that: The photoluminescent device contains the manganese-containing organic-inorganic hybrid material prepared by the method according to any one of claims 1 to 6 and / or the fluorescent material according to claim 7.

11. An optical device, comprising the manganese-containing organic-inorganic hybrid material prepared by the method according to any one of claims 1 to 6 and / or the fluorescent material according to claim 7, and / or the photoluminescent device according to claim 10.